#TITLE_ALTERNATIVE# - T B Utomo (NIM : 232 99 090),
Abstract: Wireless Local Area Network (WLAN) refered to IEEE802.11 standard actualy provide for three variation of the Physical layer . This include Direct Sequence Spread Spectrum (DSSS), Frequency Hopping (FH) and Infrared (IR) for operation in the 2.4 GHz Band of Industrial Scientific and Medical (ISM) Unlicenced Band. A data rate of 1 Mbps and spreading code of 11 Mbps is used, this gives a processing gainratio of 11:1 (code:data). This results in channel width of 22 MHz. Two channels are operated at the same time, with spacing of 30 MHz. The system has a tranceiver that can cover a path loss of 0 to 100 dB. This spectral mask requirements conforms to the IEEE 802.11 for transmission. The side lobe is at least 30 dB down from the main lobe. The output power of each channel is +18 dBm. The full spread spectrum system is represented in SystemView simulator. System with typical frequency of 1 Mbps and 2.4 GHz is scaled to 1 Mbps and 350 MHz.This will permit a faster simulation. Performance of systems subject to effects due to Additive White Gaussian Noise (AWGN), tone jamming and multipath environment by observe each the Bit Error Rate (BER).